Acral lentiginous melanoma – Is inflammation the missing link?. (December 2017) - Al-Hassani, F.; Chang, C.; Peach, H.
Abstract: We propose that repetitive chronic microtrauma, in susceptible individuals, is a significant causative factor in the development of acral lentiginous melanoma (ALM). This observational study documents a possible correlation between anatomical site of ALM and recognised high-pressure sites on the plantar foot. The pattern of distribution not only matches the gait analysis pattern, but the concentration of cases correlates with the zones of highest pressure. The surface area distribution also highlights a discrepancy between surface area affected and incidence of ALM for a purely direct causal link, suggesting another causative factor. This hypothesis is consistent with other known features of ALM, particularly age of onset in the sparing of glabrous skin, which is not subjected to repetitive shearing or direct pressure forces.